'Don't Leave Before You Understand': Supporting Master's Candidates in Business Studies - Winberg, Christine; Ntloko, Ncedo; Ncubukezi, Tabisa (Critical Studies in Teaching and Learning, 2023)
Postgraduate studies in business faculties pose particular challenges to candidates who have come from practically-oriented undergraduate programmes, particularly those that adopt a 'technical-rational' approach towards the improvement of business practices or organisational efficiency. Research studies in the applied business fields usually expect that the candidate will take a more sociological approach, or be able to work within socio-historical or political frameworks (Hordern, 2014). Candidates who are enrolled for postgraduate business studies have to negotiate this complex transition. The focus of this paper is how candidates acquire the necessary academic and social practices for theorising their research, for conducting research activities and writing up their research findings in Masters level applied business studies. We selected candidates who had experienced difficulties throughout their Masters studies and who had successfully completed, or who were close to completion, despite initial difficulty for narrative interviews. The interview data were analysed with a view to establishing the practices that supported successful transition from practice-based undergraduate business degrees to postgraduate studies in the field. This paper concludes with suggestions for supervisory practices that have the potential to support successful postgraduate research in applied business studies.